Restoration of Livestock Services in Conflict and Drought Affected Areas of Ethiopia (RESTORE) baseline study: Field researcher manual - Alemayehu, Gezahegn; Alemu, Biruk G.; Gelan, Eyob; Berhe, Tsega; Adie, Aberra; Berhanu, Dagim; Lemma, Mamusha; Desta, Hiwot; Temesgen, Wudu; Gizaw, Solomon; Knight-Jones, Theodore J.D. (International Livestock Research Institute, 2025)
This manual is produced for use by field officers (enumerators), supervisors, and study coordinators involved in the baseline survey for the RESTORE project. It helps to understand the goals of the project, the research tools, and your role as a researcher. You can take notes in your copy during the training and use it as a reference while working in the field. The document contains hyperlinks, so is best viewed digitally, but you can print the information you need for reference.